2016
DOI: 10.1039/c6ra04015b
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of 316L and 304 stainless steels exposed to industrial-marine-urban environment: field study

Abstract: The present investigation extensively compares the pitting corrosion behavior and mechanical stability of 316L and 304 stainless steels (SS) exposed to an Industrial-Marine-Urban (IMU) environment for 3 years from April 2012–March 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 50 publications
2
22
0
1
Order By: Relevance
“…Below this threshold the corrosion rate of carbon steel samples was found to be independent of the Cl − deposition rate. The role of critical concentration of Cl − in the formation of akaganeite was also recently observed by Dhaiveegan et al, where the akaganeite corresponding Raman band appeared only after 2 years of exposure of 316 L and 304 stainless steels to industrial-marine-urban environment [81]. It was also showed that the characteristics of the rust layer on mild steel depend on the atmosphere salinity (chlorine ion deposition rate).…”
Section: Resultssupporting
confidence: 56%
“…Below this threshold the corrosion rate of carbon steel samples was found to be independent of the Cl − deposition rate. The role of critical concentration of Cl − in the formation of akaganeite was also recently observed by Dhaiveegan et al, where the akaganeite corresponding Raman band appeared only after 2 years of exposure of 316 L and 304 stainless steels to industrial-marine-urban environment [81]. It was also showed that the characteristics of the rust layer on mild steel depend on the atmosphere salinity (chlorine ion deposition rate).…”
Section: Resultssupporting
confidence: 56%
“…3a and b, black line). Peak at 300 cm −1 is assigned to goethite of the 316L SS substrate [36]. After 7 days of incubation, differences between TiO 2 /HAP bilayer and composite were clearly distinguished.…”
Section: Physical and Morphological Characterizationmentioning
confidence: 96%
“…Small pits are present in the passive layer, and the penetration of the pits increases with an Fig. 6 SEM images of 316L stainless steels exposed to the environment [80] (Copyright 2016, RSC Advances) Fig. 7 SEM images of austenitic stainless steels exposed to various high temperatures [84] (Copyright 2017, Elsevier) increasing chloride-ion concentration.…”
Section: Surface Morphology and Chemical Compositionmentioning
confidence: 99%